Evolution of the United Nations Peacekeeping Research: A Visualized Bibliometrics Study - Xiaojing Wang; Yuqing Geng; Xinying Jiang; Qinjun Xiang; Mingyu Song (Complexity)
The United Nations peacekeeping has recently played a more proactive role in maintaining global peace and security. However, the majority of the literature lacks a comprehensive, visualized bibliometric analysis and forecast for emerging fields. This study employed CiteSpace to conduct a bibliometric analysis of 937 publications between 2000 and 2022, aiming to gain a comprehensive understanding of the research status and development trend of the UN peacekeeping research. Via the fundamental and in-depth analysis, we find that the overall publication trend has experienced a nonlinear but steady upward evolution due to the mature and stable cooperation research network established at the country, institution, and author levels; representative keywords such as peace, intervention, and civil war illustrate the dynamic evolution characteristics of hotspots and frontiers. This article is innovative because we use fundamental and in-depth analysis to depict a panorama of this field; identify the hotspots through macro-, meso-, and microlevels; and provide the knowledge framework with future research characteristics, which help scholars continue future research effectively.